If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1x + 2x + -4) + (-2x + 4x + -2) = y Reorder the terms: (-4 + -1x + 2x) + (-2x + 4x + -2) = y Combine like terms: -1x + 2x = 1x (-4 + 1x) + (-2x + 4x + -2) = y Remove parenthesis around (-4 + 1x) -4 + 1x + (-2x + 4x + -2) = y Reorder the terms: -4 + 1x + (-2 + -2x + 4x) = y Combine like terms: -2x + 4x = 2x -4 + 1x + (-2 + 2x) = y Remove parenthesis around (-2 + 2x) -4 + 1x + -2 + 2x = y Reorder the terms: -4 + -2 + 1x + 2x = y Combine like terms: -4 + -2 = -6 -6 + 1x + 2x = y Combine like terms: 1x + 2x = 3x -6 + 3x = y Solving -6 + 3x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3x = 6 + y Combine like terms: -6 + 6 = 0 0 + 3x = 6 + y 3x = 6 + y Divide each side by '3'. x = 2 + 0.3333333333y Simplifying x = 2 + 0.3333333333y
| 16t^2+4t=600 | | m+1=m+2 | | -2y^2-200y+3200=0 | | 3r^2-6r=144 | | r/3+8=11 | | 4t^2+t-150=0 | | x=30-40 | | d=16(2.5) | | 2-x/3=-8 | | 2y^2-2y+32=0 | | 2085000000.00+5550000x=2500000000 | | 31-4x=0 | | y-(-2)=-1/2(x-1) | | d=12(2.5) | | 8+x/7=-3 | | (7+y)(5y-6)=0 | | x=42-28 | | 6x-3(x+4)= | | x-6/5+7=0 | | -x/3-6=-9 | | 2n+8=3n+3 | | y=-2x^2+28x-7 | | d=12(3.5) | | 1-125x^3=0 | | Y=6x^4-13x^3-5x^2 | | -16t^2+1600t=0 | | f(x)=18-x | | n+5/3=-10 | | 2++++5= | | 24/40x | | 100=2.368068834x+x | | -2a+10=20 |